Outcomes of Discectomy by Using Full-Endoscopic Visualization Technique via the Transcorporeal and Transdiscal Approaches in the Treatment of Cervical Intervertebral Disc Herniation: A Comparative Study. (30th May 2020) - Ren, Youliang; Yang, Junsong; Chen, Chien-Min; Liu, Kaixuan; Wang, Xiang-Fu; Wei, Jian-Min; Shi, Lei; Liu, Wen; Jiang, Haitao; Zhou, Hang; Li, Shen; Xu, Zhou; et al.
Abstract : Objective . To compare the difference in clinical and radiographic outcomes between anterior transcorporeal and transdiscal percutaneous endoscopic cervical discectomy (ATc-PECD/ATd-PECD) approaches for treating patients with cervical intervertebral disc herniation (CIVDH). Method . We selected 77 patients with single-segment CIVDH and received ATc-PECD or ATd-PECD in the Second Affiliated Hospital of Chongqing Medical University between March 1, 2010, and July 1, 2015. 35 patients suffered from ATc-PECD, and there were 42 patients in the ATd-PECD group. Obtaining the data of 1, 3, 6, 12, and 24 months postoperatively, the VAS for neck and arm pain and the modified MacNab criteria were used to evaluate the clinical outcomes, comparing radiographic outcomes and complications of these two groups. Results . We found that the mean operative time was significantly longer in the ATc-PECD group (P < 0.05 ). At the 2-year follow-up, the mean VAS score for neck and arm pain was significantly decreased in both two groups. There was no significant difference in the VAS score for arm pain and neck pain between the two groups at the 2-year follow-up (P = 0.783 and P = 0.785, respectively). For the ATc-PECD group, the difference in the height of IVS or vertebral body was significant between the preoperative and postoperative groups (P < 0.05, respectively). For the ATd-PECD group, there was only a significant decrease in the height of the IVS (P < 0.05 ); the decrease in the surgical vertebral body was not significant between the preoperative and postoperative groups (P > 0.05 ). Conclusion . In the 2-year follow-up, there is no significant difference in the clinical outcomes between the 2 approaches. While the longer time was consumed in the ATc-PECD group, the lower rate of disc collapse and recurrence is notable. Additionally, when the center diameter of tunnel was limited to 6 mm, the bony defect can be healed without the occurrence of the collapse of the superior endplate, and ATc-PECD may be preferable in the endoscopic treatment of CIVDH.